2019
DOI: 10.12806/v18/i1/r9
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Lead: Perceptions of Undergraduate Leadership Minor Programs

Abstract: As leadership continues to be a targeted outcome of student learning within higher education, university faculty are left with the challenge of how to best teach and develop leadership in college students. Students are a key component of undergraduate leadership education; their motivations, learning goals, and understanding of their experiences in leadership programs. However, the research on undergraduate leadership programs from the students' perspectives is relatively scarce and limited in scope. To addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Leadership learning has been shown to transfer from leadership development training for working professionals into the work environment (Brue & Brue, 2016;Coloma et al, 2012;Patton et al, 2103), and some evidence exists that leadership learning can effectively transfer from a structured undergraduate leadership program into the workplace (Mitchell & Daugherty, 2019;Soesbe, 2012 learning displayed results in which students learned more about themselves or became more confident as leaders (Bond & Sterrett, 2014;Chesnut & Tran-Johnson, 2013;Eich, 2008;Soesbe, 2012). Alumni of an undergraduate leadership program at a liberal arts institution believed the strengths assessment and other similar assessments led to greater selfawareness and a better understanding of the way they lead others (Soesbe, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Leadership learning has been shown to transfer from leadership development training for working professionals into the work environment (Brue & Brue, 2016;Coloma et al, 2012;Patton et al, 2103), and some evidence exists that leadership learning can effectively transfer from a structured undergraduate leadership program into the workplace (Mitchell & Daugherty, 2019;Soesbe, 2012 learning displayed results in which students learned more about themselves or became more confident as leaders (Bond & Sterrett, 2014;Chesnut & Tran-Johnson, 2013;Eich, 2008;Soesbe, 2012). Alumni of an undergraduate leadership program at a liberal arts institution believed the strengths assessment and other similar assessments led to greater selfawareness and a better understanding of the way they lead others (Soesbe, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Student alumni's use of leadership language and the application of leadership expertise to daily experiences were discovered by Mitchell and Daugherty (2019). Furthermore, student graduates reported job advancement and greater marketability as a result of using their leadership knowledge and abilities throughout their professions (Mitchell & Daugherty, 2019). Beatty et al (2021b), similar to White and Guthrie (2016), found that reflection is an important part of developing self-awareness for undergraduate leadership learners.…”
Section: Leadership Learning Outcomesmentioning
confidence: 97%
“…Outcomes of leadership education, thus, extend beyond undergraduate studies. Student alumni’s use of leadership language and the application of leadership expertise to daily experiences were discovered by Mitchell and Daugherty (2019). Furthermore, student graduates reported job advancement and greater marketability as a result of using their leadership knowledge and abilities throughout their professions (Mitchell & Daugherty, 2019).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…UTAs in a small group experience can positively affect a student’s ability to develop mental schemas through which new knowledge can be acquired (Kwok, Jian, & Vogel, 2002). Face-to-face interaction with peers is especially important in leadership education, as Mitchell and Daugherty’s (2019) perception study of students and alumni (N = 130) from an academic leadership minor program revealed that students felt, as leaders, they benefitted most in courses where they could interact with their peers in person.…”
Section: Organization Of Current Papermentioning
confidence: 99%